ANALISIS PRAGMATIK KATA BAKA DALAM KOMUNIKASI LISAN BAHASA JEPANG - , LILI FEBRIYANI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study discusses the use of the word baka in Japanese oral communication. The word baka is a Japanese word that mean stupid or fool, whose literal meaning tends to be negative. The purpose of this study was to determine and describe any pragmatic meaning of the word baka embodied in oral communication. This study is included in the scope of pragmatic studies using the theory of Searle speech act to describe the form and the pragmatic meaning of the word baka. The pragmatic meaning of the word baka was analyzed and described by the qualitative descriptive method. Based on the results of research that takes the data from the Japaneselanguage dramas, it is known that pragmatically the word baka is included in three illocutionary speech acts, namely assertive, directive, and expressive. In the assertive speech act, pragmatic meaning of the word baka covers stated / asserted, express opinion, argue a statement, and boasting. In the directive, pragmatic meaning of the word baka covers giving advice and commands (imperatives). In the expressive, pragmatic meaning of the word baka covers criticism / underestimating / blaming, saying thank you (touched), apology / forgiving, praising (awe), and self-deprecating.